Functional intermuscular reduction in spasticity for people with multiple sclerosis. Issue 1 (January 2022) - Miller, Bobbette J; Kolobe, Thubi HA; Larson, Rebecca D; Pribble, Brian A; Pardo, Gabriel; James, Shirley A
Background: Eighty-five percent of people with multiple sclerosis (MS) incur gait impairments debilitating enough to significantly impact their function. Objectives: The aim of this study was to determine if a novel combination of intermuscular electrical stimulation, followed by functional electrical stimulation combined with supported bodyweight treadmill training, would improve gait, decrease spasticity and fatigue, and improve muscle strength. Methods: Using a pre-post experimental design, we implemented this combination six-week protocol in 16 individuals with MS. We completed summary statistics and longitudinal pre-post results using Wilcoxon sign rank tests with Bonferroni adjustment. Results: Participants responded with median increases of 29.4 feet ( p  < 0.0001) during the Six Minute Walk Test, median decreases of 0.7 s ( p  = 0.0011) in the 25-Foot Walk Test, median increases of 3.8 toe taps to fatigue ( p  = 0.0306) and median increases of 5.0 heel raises ( p  = 0.0093). Significant changes were noted in the Modified Ashworth Scale, both after intermuscular electrical stimulation (median change = −0.5 p  = 0.0039) and after treadmill walking (median change = −0.5, p  < 0.0005). Conclusions: Results of this novel protocol suggest this intervention combination has the potential to decrease spasticity, and improve gait speed and endurance in individuals with MS. Observed changes in mobility occurred without accompanying increases in fatigue.